Vida cotidiana e identidad de la region de Comalcalco en el contexto mesoamericano - Miriam Judith Gallegos Gómora (Nuevo mundo - Mundos Nuevos, 2018)
Archeology points out that the city of Comalcalco developed mainly between 550 and 900 AD, during which the features that would identify its population were delineated. To learn about the social process that shaped this community, we analyze the objects the people made, used, exchanged and discarded, as well as the spaces they built. The review of its sources of raw materials, technology, mortuary customs, physical characteristics and conditions, allow us to investigate how the social relations and behavior patterns of its population were established and reinforced.